Excitation energy migration dynamics in upconversion nanomaterials. (16th September 2014) - Tu, Langping; Liu, Xiaomin; Wu, Fei; Zhang, Hong
Abstract : Excitation energy migration in a rare earth ions doped upconversion nanoparticle. Abstract : Recent efforts and progress in unraveling the fundamental mechanism of excitation energy migration dynamics in upconversion nanomaterials are covered in this review, including short- and long-term interactions and other interactions in homogeneous and heterogeneous nanostructures. Comprehension of the role of spatial confinement in excitation energy migration processes is updated. Problems and challenges are also addressed.